Determinants Analysis Of Indonesia's Foreign Exchange Reserves In 1990-2023 - Putu Krishna Candrawinata; I Nyoman Wahyu Widiana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
oreign exchange reserves are one of the key indicators in international trade, reflecting the fundamental strength of a country's economy. They serve as a benchmark to assess the robustness of a nation's economic condition and indicate its ability to engage in international trade. Several factors influence Indonesia's foreign exchange reserves, including export value, exchange rate, and foreign direct investment (FDI). This study aims to analyze the simultaneous impact of export value, exchange rate, and FDI on Indonesia's foreign exchange reserves, as well as their partial effects. The data analysis technique employed in this research is multiple linear regression. The findings reveal that export value, exchange rate, and FDI significantly influence Indonesia’s foreign exchange reserves simultaneously. Partially, export value and exchange rate have a positive and significant impact, while FDI has a positive but statistically insignificant effect. It can be concluded that increasing export value and maintaining exchange rate stability play a crucial role in sustaining and enhancing Indonesia's foreign exchange reserves.